VULNERABILITY AND HIERARCHICALISM - Keenan, James F. (Asian Horizons, 2020)
This essay moves through the different stages of the sexual abuse crisis as a call to conversion, looking first at the sinful spectre of sexual abuse, by not only priests and their culture of clericalism, but also by bishops and their very distinctive, formative culture of hierarchicalism that teaches many to be dominant, and non-accountable. Investigating notions of vulnerability that are not about weakness but rather about the capacity to respond as Jesus did, the essay highlights the effectiveness of a richer understanding of vulnerability to counter the vices that produced the sexual abuse crises around the world.